Changes in Plant-Based Diet Quality and Total and Cause-Specific Mortality. Issue 12 (17th September 2019) - Baden, Megu Y.; Liu, Gang; Satija, Ambika; Li, Yanping; Sun, Qi; Fung, Teresa T.; Rimm, Eric B.; Willett, Walter C.; Hu, Frank B.; Bhupathiraju, Shilpa N.
Abstract : Background: Plant-based diets have been associated with lower risk of type 2 diabetes mellitus and cardiovascular disease (CVD) and are recommended for both health and environmental benefits. However, the association between changes in plant-based diet quality and mortality remains unclear. Methods: We investigated the associations between 12-year changes (from 1986 to 1998) in plant-based diet quality assessed by 3 plant-based diet indices (score range, 18–90)—an overall plant-based diet index (PDI), a healthful PDI, and an unhealthful PDI—and subsequent total and cause-specific mortality (1998–2014). Participants were 49 407 women in the Nurses' Health Study (NHS) and 25 907 men in the Health Professionals Follow-Up Study (HPFS) who were free from CVD and cancer in 1998. Multivariable-adjusted Cox proportional-hazards models were used to estimate hazard ratios (HRs) and 95% CIs. Results: We documented 10 686 deaths including 2046 CVD deaths and 3091 cancer deaths in the NHS over 725 316 person-years of follow-up and 6490 deaths including 1872 CVD deaths and 1772 cancer deaths in the HPFS over 371 322 person-years of follow-up. Compared with participants whose indices remained stable, among those with the greatest increases in diet scores (highest quintile), the pooled multivariable-adjusted HRs for total mortality were 0.95 (95% CI, 0.90–1.00) for PDI, 0.90 (95% CI, 0.85–0.95) for healthful PDI, and 1.12 (95% CI, 1.07–1.18) for unhealthful PDI. Among participants with the greatest decrease (lowest quintile), the multivariable-adjusted HRs were 1.09 (95% CI, 1.04–1.15) for PDI, 1.10 (95% CI, 1.05–1.15) for healthful PDI, and 0.93 (95% CI, 0.88–0.98) for unhealthful PDI. For CVD mortality, the risk associated with a 10-point increase in each PDI was 7% lower (95% CI, 1–12%) for PDI, 9% lower (95% CI, 4–14%) for healthful PDI, and 8% higher (95% CI, 2–14%) for unhealthful PDI. There were no consistent associations between changes in plant-based diet indices and cancer mortality. Conclusions: Improving plant-based diet quality over a 12-year period was associated with a lower risk of total and CVD mortality, whereas increased consumption of an unhealthful plant-based diet was associated with a higher risk of total and CVD mortality. Abstract : Supplemental Digital Content is available in the text.